Understanding Microtuning Through Recording Analysis: The Transcription and Analysis of Microtuning in Five Recordings from a Variety of Musical Traditions - Brook, Taylor (Intersections, 2021)
This article presents five computer-assisted analyses of musical recordings with a focus on microtuning, describing the details of pitch at sub-semitone level. Microtuning encompasses intonation, tuning systems, pitch inflection, vibrato, and sliding tones. As such, the article focuses on the analysis of recorded music and considers a wide variety of musical traditions: an American folk song, an Ainu lament, a Christian Ethiopian devotional, a Beethoven string quartet, and a Tom Waits song. This article asks how music notation might most effectively capture microtuning in transcriptions and how the analysis of recordings, rather than musical scores, might enrich pedagogy and practice in music theory, performance, and composition.